Oral health between systemic health and public health - Franco-Giraldo, Álvaro (Universidad y Salud, 2021)
Introduction: Despite the implementation of diverse strategies to address oral health problems, they still lack an integral vision of both the human being and health practice. Objective: To analyze oral health as a medical and professional practice from an interpretative and critical perspective. The Colombian context was highlighted as well as the association of oral health with systemic and public health. Materials and methods: A documentary narrative review was conducted, searching the Boolean terms: (periodontitis or oral pathology) and (systematic diseases). The guiding question used was, “How does oral pathology affect chronic non-communicable diseases?” and the search included the last five years. Results: Associations of oral health with systemic health, CNCDs (diabetes, cardiovascular diseases, eclampsia, perinatal disease, and Alzheimer’s), among others, were identified. Conclusions: A biunivocal relationship between periodontal disease and chronic non-communicable diseases is consistent in the literature, but causal relationships are difficult to conclude. Both public health strategies and an articulation of the interprofessional health practice are proposed.